Evaluasi Program Pemberian Tablet Tambah Darah pada Remaja Putri di Wilayah Kerja Puskesmas Kebonsari Kabupaten Madiun - Almas Ata Afiqoh Ningrum (Jurnal Ilmu Kesehatan dan Gizi, 2025)
Efforts to reduce the prevalence of anemia in adolescent girls are carried out by supplementing with Iron Tablets. This research aims to evaluate the program of providing iron tablets to adolescent girls in the work area of the Kebonsari Health Center, Madiun Regency. The research was conducted qualitatively with indepth interview techniques and Focus Group Discussions (FGD), informants were determined by purposive sampling totaling 16 people. The research was conducted in July-September 2023 at the Health Office, Madiun Regency Pharmacy Installation, Kebonsari Health Center, SMPN 2 Kebonsari and MAN 1 Madiun. The data analysis technique used triangulation, processed using reduction and presented in the narrative text. The results of the study were reviewed based on the book "Guidelines for Prevention and Management of Anemia in Adolescent Girls 2016" showing that several aspects were appropriate, including human resources, fund allocation, preparation, distribution, recording and reporting, scope of activities and accuracy of targets and distribution. While aspects that were not appropriate included facilities and infrastructure, monitoring and timeliness. Similar research should be conducted in other schools in the working area of the Kebonsari Health Center, Madiun Regency so that the effectiveness of the implementation of the program can be evaluated and improved.